Genome-wide transcriptome directed pathway analysis of maternal pre-eclampsia susceptibility genes - Yong, H.; Melton, P.; Johnson, M.; Freed, K.; Kalionis, B.; Murthi, P.; Brennecke, S.; Keogh, R.; Moses, Eric (2015)
Background: Preeclampsia (PE) is a serious hypertensive pregnancy disorder with a significant genetic component. Numerous genetic studies, including our own, have yielded many susceptibility genes from distinct functional groups. Additionally, transcriptome profiling of tissues at the maternal-fetal interface has likewise yielded many differentially expressed genes. Often there is little overlap between these two approaches, although genes identified in both approaches are significantly associated with PE. We have thus taken a novel integrative bioinformatics approach of analysing pathways common to the susceptibility genes and the PE transcriptome. Methods: Using Illumina Human Ht12v4 and Wg6v3 BeadChips, transcriptome profiling was conducted on n = 65 normotensive and n = 60 PE decidua basalis tissues collected at delivery. The R software package libraries lumi and limma were used to preprocess transcript data for pathway analysis. Pathways were analysed and constructed using Pathway Studio. We examined ten candidate genes, which are from these functional groups: activin/inhibin signalling - ACVR1, ACVR1C, ACVR2A, INHA, INHBB; structural components - COL4A1, COL4A2 and M1 family aminopeptidases - ERAP1, ERAP2 and LNPEP.Results/Conclusion: Major common regulators/targets of these susceptibility genes identified were AGT, IFNG, IL6, INHBA, SERPINE1, TGFB1 and VEGFA. The top two categories of pathways associated with the susceptibility genes, which were significantly altered in the PE decidual transcriptome, were apoptosis and cell signaling (p < 0.001). Thus, susceptibility genes from distinct functional groups share similar downstream pathways through common regulators/targets, some of which are altered in PE. This study contributes to a better understanding of how susceptibility genes may interact in the development of PE. With this knowledge, more targeted functional analyses of PE susceptibility genes in these key pathways can be performed to examine their contributions to the pathogenesis and severity of PE.